Gastrointestinal Disease in Malnourished Children - Michael Gracey (Indonesian Pediatric Society, 1975)
In communities where malnutrition is common, gastrointestinal diseases are prominent and contribute largely to unfavourable morbidity and mortality statistics. Patterns of gastrointestinal disease were studied in two such cotnmunities; Aboriginal children in Western Australia and children admitted to the Dr. Cipto Mangunkusumo General Hospital, Jakarta.Two hundred and fifty one (251) young Aborigines were studied. Forty percent of them malnourished, 37% were anaemic and more than 50% had enteric pathogens in their stools. Sugar intolerance was also common (25%). Similar clinical features are seen in the children from Jakarta but more severe forms of malnutrition and gross vitamin deficiency occurred more often.Thirteen of the Aboriginal children died; at necropsy the most remarkable finding wass fatty infiltration of the liver which some cases was extreme. This, of course, is characteristic of protein-calorie malnutrition add has been well documented in other studies. Other pathological findings included severe purulent infections, septic infarcts, haemolysis, acanthocytosis, thrombocytopenia and vascular catastrophes.